Auditory and Nociceptive Stimuli Responses in the Electroencephalogram - Melia, U.; Vallverdú, M.; Clariá, F.; Valls-Solé, J.; Caminal, P. (Methods of Information in Medicine, 2015)
Introduction: This article is part of the Focus Theme of Methods of Information in Medicine on “Biosignal Interpretation: Advanced Methods for Neural Signals and Images“.Objectives: An efficient way to investigate the neural basis of nociceptive responses is the analysis of the event-related brain potentials (ERPs). The main objective of this work was to study how adaptation and fatigue affect the ERPs to stimuli of different modalities, by characterizing the responses to infrequent and frequent stimulation in different recording periods.Methods: In this work, series of averaged EEG epochs recorded after thermal, electrical and auditory stimulation were analyzed with time-frequency representation and non-linear measures as spectral entropy and auto-mutual information function. The study was performed by considering the traditional EEG frequency bands.Results: The defined measures presented a statistical significance p-value < 0.01 and accuracy higher than 60% by differentiating windows of response to infrequent (I) and frequent (F) stimuli between the start and end of the EEG recording.Conclusions: These measures permitted to observe some aspects of the subject’s adaptation and the nociceptive response.
Keywords: Non-linear dynamics; time-frequency analysis; EEG processing; evoked potential